PRESSURE-INDUCED IONIZATION OF NICKEL DEEP LEVELS IN COMPENSATED SILICON UNDER HYDROSTATIC PRESSURE: A STATIC REGIME STUDY - R. Khamidov; J. Nematullaev (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract:The piezoresistance effect in n-type silicon compensated with nickel (n-Si:(P,Ni)) has been investigated under static hydrostatic pressure conditions. The static regime, characterized by slow pressure application rates (<0.2 GPa/s), ensures complete thermal equilibrium, eliminating adiabatic heating artifacts. Measurements up to 0.6 GPa reveal a monotonic and fully reversible decrease in electrical resistivity. Hall effect analysis demonstrates that this reduction is governed predominantly by a pressure-induced increase in free electron concentration. The effect is explained by the decrease in ionization energy of deep nickel acceptor levels under hydrostatic compression. The piezoresistance coefficient is derived as , where the first term, representing the concentration contribution, dominates. These findings establish that the equilibrium deformation response in compensated silicon with deep levels is controlled by pressure-modulated carrier density through deep-level ionization.